Effects of combined use of compound acidifiers and plant essential oils in feed on the reproductive performance and physiological status of Xianjv chickens - Zhaobin Wang; Caiyun Zhang; Huicheng Wang; Tiantian Gu; Yong Tian; Zhuoya Gu; Li Chen; Tao Zeng; Lizhi Lu; Wenwu Xu (Poultry Science)
This study investigates the effects of combined compound acidifiers and plant essential oils on the production performance, egg quality, and health parameters of Xianjv chickens. A total of 240 healthy 34-week-old Xianjv chickens were randomly divided into 5 groups and given 5 different feed additives: a control group with a basal diet, and four experimental groups with varying doses of compound acidifiers (CA) and essential oils (EO). The results revealed that the addition of compound acidifiers and essential oils did not significantly affect average daily feed intake, egg production rate, or feed-to-egg ratio. However, supplementation with CA and EO significantly improved eggshell strength, albumen height, and Haugh unit, enhancing overall egg quality. Additionally, the combination of these additives enhanced serum antioxidant capacity by increasing levels of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT), while reducing malondialdehyde (MDA) levels. It also lowered inflammatory cytokines such as interleukin-2 (IL-2) and interleukin-6 (IL-6) and improved intestinal health by enhancing digestive enzyme activities, including trypsin and lipase, in the duodenum and jejunum. The study concludes that the combined use of compound acidifiers and plant essential oils offers a promising alternative to antibiotics in poultry feed, improving egg quality and supporting better health status in Xianjv chickens. Nevertheless, careful optimization of the dosages and combinations is necessary to maximize their benefits without adversely affecting the birds' physiological balance.